Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/9201979
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24 Weeks of Growth Hormone Treatment on Bone Microstructure and Volumetric Bone Density in Patients with Childhood-Onset Adult GH Deficiency

Abstract: Objective. Adults with childhood-onset growth hormone deficiency (CO AGHD) have prominently impaired volumetric bone density (vBMD) and bone microarchitecture. Effects of recombinant human growth hormone (rhGH) on bone microarchitecture in CO AGHD were insufficiently evaluated. e objective of this study is to assess the effects of rhGH on bone microarchitecture and vBMD in CO AGHD patients. Design. In this single-center prospective study, nine CO AGHD patients received rhGH treatment for 24 weeks. High-resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The effects of long-term rhGH replacement therapy on BMD in AGHD patients are still in debate. A previous study in our center found that CO AGHD patients treated with rhGH replacement therapy for 24 weeks showed a significant increase in bone turnover markers and a significant improvement in bone microarchitecture of the distal tibia [29]. Holmes et al found that CO AGHD patients had no change in cortical and overall bone mass during the first 6 months of rhGH replacement therapy, while vertebral trabecular vBMD increased at 6 months, followed by a steady increase in BMD at all sites over the next 12-18 months [30].…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…The effects of long-term rhGH replacement therapy on BMD in AGHD patients are still in debate. A previous study in our center found that CO AGHD patients treated with rhGH replacement therapy for 24 weeks showed a significant increase in bone turnover markers and a significant improvement in bone microarchitecture of the distal tibia [29]. Holmes et al found that CO AGHD patients had no change in cortical and overall bone mass during the first 6 months of rhGH replacement therapy, while vertebral trabecular vBMD increased at 6 months, followed by a steady increase in BMD at all sites over the next 12-18 months [30].…”
Section: Accepted Manuscriptmentioning
confidence: 80%